Erythema Induratum of Bazin: A Rare Finding in an Old Woman with Subcutaneous Nodules in the Lower Limbs - Islam, Nahida; Islam, Md Shahidul; Sharmeen, Atia; Sarker, Susthir (Community Based Medical Journal, 2023)
Erythema induratum of Bazin (EIB) is a chronic nodular eruption that frequently occurs on lower legs of young or middle-aged women. The clinical manifestations of EIB revealed various dermatological disorders that can be easily leads to misdiagnosis. We report a case of a 50-year-old woman who initially presented with EIB. The histopathological specimen was collected from her medial aspect of let leg. The epidermis is unremarkable. The dermis shows fibro fatty tissue, skin adnexae and foci of granuloma with Langhans type of giant cells and some lymphocytic infiltration in the deep dermis which was suggestive of erythema induratum. Her lesions responded to antitubercular therapy (ATT). This case study may help extend the therapeutic regimens for cutaneous tuberculosis. CBMJ 2023 January: Vol. 12 No. 01 P: 121-123